Diagnosing technical condition of gas turbine engines by building a binary tree - Якушенко, О.С. (Proceedings of National Aviation University, 2007)
In the paper the problem of binary trees using for identification of aircraft gas turbine engines technical condition is considered. The results of the method using for aircraft gas turbine engines technical condition identification are given.